2015
DOI: 10.1103/physrevb.92.064412
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion dynamics in chiral ferromagnets

Abstract: We study the dynamics of skyrmions in Dzyaloshinskii-Moriya materials with easy-axis anisotropy. An important link between topology and dynamics is established through the construction of unambiguous conservation laws obtained earlier in connection with magnetic bubbles and vortices. In particular, we study the motion of a topological skyrmion with skyrmion number Q = 1 and a non-topological skyrmionium with Q = 0 under the influence of an applied field gradient. The Q = 1 skyrmion undergoes Hall motion perpen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 31 publications
(70 reference statements)
3
151
0
Order By: Relevance
“…Moreover, the significant effects of the uniaxial stress on the stabilization of the skyrmion lattice have been revealed in earlier works [12][13][14][15]. On the skyrmion dynamics, it has been suggested that the skyrmions in chiral magnets can be effectively modulated by spin-polarized current [16][17][18][19], microwave fields [20], magnetic field gradients [21,22], electric field gradients [23][24][25][26], temperature gradients [27] etc. So far, some of these manipulations have been realized in experiments [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the significant effects of the uniaxial stress on the stabilization of the skyrmion lattice have been revealed in earlier works [12][13][14][15]. On the skyrmion dynamics, it has been suggested that the skyrmions in chiral magnets can be effectively modulated by spin-polarized current [16][17][18][19], microwave fields [20], magnetic field gradients [21,22], electric field gradients [23][24][25][26], temperature gradients [27] etc. So far, some of these manipulations have been realized in experiments [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the magnetic field gradients along the y-axis direction, as shown in figure 1(a), can induce a Hall-like motion of skyrmions, showing that in addition to the main velocity along the x-axis direction (v x ) induced by the magnetic field gradient, a slight transverse velocity can also be caused along the y-axis direction (v y ) due to the damping effect. Recently, a theoretical study on the dynamics of skyrmions driven by a magnetic field gradient has been published [36], in which the skyrmion is considered as a soliton and its dynamics is analyzed by the momentum calculation.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic skyrmion can also be nucleated with the nano-patterning 39 and be converted from a domain-wall pair 25 . For the manipulation of the magnetic skyrmion, one can use the spin current 21,23 , the spin wave [40][41][42][43] , as well as the thermal gradient [44][45][46] to drive the magnetic skyrmion.…”
Section: Introductionmentioning
confidence: 99%